The periplasmic chaperone Skp prevents misfolding of the secretory lipase A from Pseudomonas aeruginosa - Papadopoulos, Athanasios; Busch, Max; Reiners, Jens; Hachani, Eymen; Baeumers, Miriam; Berger, Julia; Schmitt, Lutz; Jaeger, Karl-Erich; Kovacic, Filip; Smits, Sander H. J.; Kedrov, Alexej (Frontiers in Molecular Biosciences, 2022)
Pseudomonas aeruginosa is a wide-spread opportunistic human pathogen and a high-risk factor for immunodeficient people and patients with cystic fibrosis. The extracellular lipase A belongs to the virulence factors of P. aeruginosa. Prior to the secretion, the lipase undergoes folding and activation by the periplasmic foldase LipH. At this stage, the enzyme is highly prone to aggregation in mild and high salt concentrations typical for the sputum of cystic fibrosis patients. Here, we demonstrate that the periplasmic chaperone Skp of P. aeruginosa efficiently prevents misfolding of the lipase A in vitro. In vivo experiments in P. aeruginosa show that the lipase secretion is nearly abolished in absence of the endogenous Skp. Small-angle X-ray scattering elucidates the trimeric architecture of P. aeruginosa Skp and identifies two primary conformations of the chaperone, a compact and a widely open. We describe two binding modes of Skp to the lipase, with affinities of 20 nM and 2 µM, which correspond to 1:1 and 1:2 stoichiometry of the lipase:Skp complex. Two Skp trimers are required to stabilize the lipase via the apolar interactions, which are not affected by elevated salt concentrations. We propose that Skp is a crucial chaperone along the lipase maturation and secretion pathway that ensures stabilization and carry-over of the client to LipH.